Review of the injectate dispersion pattern during anterior quadratus lumborum block. Issue 48 (2nd December 2022) - Wu, Jin; Qin, Yifan; She, Huiyu; Ma, Rui
Abstract : Since its introduction in 2013, the anterior quadratus lumborum (QL) block (QLB) has been widely used for analgesia in abdominal, pelvic, and hip surgeries, based on the assumption that it has analgesic effects on both incisional and visceral pain. However, the mechanism of the anterior QLB remains unclear, and the results of relevant studies are contradictory. This review aimed to summarize the dispersion patterns of injectates in anterior QLB. We conducted literature searches using PubMed, Cochrane, and Embase databases. A total of 10 cadaveric or radiological studies meeting the inclusion and exclusion criteria were summarized. The dye or contrast agent spread to the thoracic paravertebral space in only 5 of the studies reviewed. Variability in the selection of injection sites relative to the anterior layer of the thoracolumbar fascia during anterior QLB implementation may explain the dispersion difference. The correct injection site of an anterior QLB is anterior to the QL muscle and between the QL muscle and the anterior layer of the thoracolumbar fascia. Further studies are needed to verify the injectate dispersion pattern during anterior QLB.